Monte Carlo Algorithm Based on Internal Bridging Moves for the Atomistic Simulation of Thiophene Oligomers and Polymers - Tsourtou, Flora D; Peroukidis, Stavros D; Peristeras, Loukas D; Mavrantzas, Vlasis G (Macromolecules, 2018)
We introduce a powerful Monte Carlo (MC) algorithm for the atomistic simulation of bulk models of oligo- and polythiophenes by redesigning MC moves originally developed for considerably simpler polymer structures and architectures, such as linear and branched polyethylene, to account for the ring structure of the thiophene monomer. Elementary MC moves implemented include bias reptation of an end thiophene ring, flip of an internal thiophene ring, rotation of an end thiophene ring, concerted rotation of three thiophene rings, rigid translation of an entire molecule, rotation of an entire molecule, and volume fluctuation. In the implementation of all moves we assume that thiophene ring atoms remain rigid and strictly coplanar; on the other hand, inter-ring torsion and bond bending angles are left fully flexible subject to suitable potential energy functions. Test simulations with the new algorithm of an important thiophene oligomer, α-sexithiophene (α-6T), at a high enough temperature (above its isotropic-to-nematic phase transition) using a new united atom model specifically developed for the purpose of this work provide predictions for the volumetric, conformational, and structural properties that are remarkably close to those obtained from detailed atomistic molecular dynamics (MD) simulations using an all-atom model. The new algorithm is particularly promising for addressing the rich (and largely unexplored) phase behavior and nanoscale ordering of very long (also more complex) thiophene-based polymers which cannot be accessed by conventional MD methods due to the extremely long relaxation times characterizing chain dynamics in these systems.